DEVELOPMENT OF BUSINESS PLANNING LEARNING VIDEOS FOR STUDENTS OF SMKN 1 MUARO JAMBI (Indonesian Journal of Educational Development (IJED), 2024)
To foster interest in entrepreneurship, vocational school students need to be taught about business planning. This business planning material is packaged in the form of learning videos so that learning can achieve maximum results. The aim of this research is to describe the planning, design and development of learning videos, assess the theoretical, conceptual and practical feasibility of learning videos, describe peer responses and describe the attractiveness of business planning learning videos. The research method used is Research and Development. The research subjects were class X BDP students at SMKN 1 Muaro Jambi. The development model that is used as a reference is the Trollip and Allesi (2001) development model with the stages of Planning, Designing and Developing. The research results show that the material expert validation results are 96% in the very feasible category. And the media expert validation results were 85% in the very feasible category. And the teacher's response was obtained with a score of 90% in the very appropriate category. Then the field trial obtained a score of 91.5% in the very high category. So the business planning learning video is suitable for use by students of SMKN 1 Muaro Jambi as an interesting learning media with a score of 89.7%.